2021
DOI: 10.1684/orthodfr.2021.42
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic treatment and aligners, which protocol?

Abstract: Introduction : Les technologies numériques dentaires de conception, simulation et fabrication sont en constante évolution. Il est possible de simuler numériquement des mouvements dentaires, ainsi que des déplacements des deux arcades et de réaliser des gouttières thermoformées fabriquées à partir de cette simulation. Objectif : Les auteurs présentent le couplage de la numérisation 3D intra-buccale avec la radiographie 3D de basses doses d'irradiation qui permet de réaliser un setup chirurgical très précis, de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 5 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The articles selected in the present study showed that the aligners are created by computer software, require only one impression, require few complementary exams, and allow excellent predictability of the treatment, when used within their indications [1,2]. They have a satisfactory aesthetic level, are comfortable, easy to clean, cause less trauma when compared to conventional fixed appliances, are less uncomfortable for patients since they can be removed and placed back without difficulty by the patient, and demonstrate excellent results.…”
Section: Major Findings -Aligner Plates In Orthodonticsmentioning
confidence: 98%
See 3 more Smart Citations
“…The articles selected in the present study showed that the aligners are created by computer software, require only one impression, require few complementary exams, and allow excellent predictability of the treatment, when used within their indications [1,2]. They have a satisfactory aesthetic level, are comfortable, easy to clean, cause less trauma when compared to conventional fixed appliances, are less uncomfortable for patients since they can be removed and placed back without difficulty by the patient, and demonstrate excellent results.…”
Section: Major Findings -Aligner Plates In Orthodonticsmentioning
confidence: 98%
“…There are numerous options involving technologies that serve people of the most varied ages and lifestyles. Among them, the aligner plates are ideal for those who want to correct imperfections in the dental position [1]. The aligner plates are transparent acetate orthodontic appliances, used to harmonize the smile through the movement of the teeth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized clinical trial confirmed that treatment duration and chair time in mild-to-moderate cases appear to be significantly short over conventional systems [ 19 ]. There is also a lack of evidence on the use of aligners in space closure and its impact on periodontal health [ 20 ]. There is a need for evidence in conducting well-designed clinical trials.…”
Section: Introductionmentioning
confidence: 99%